2018
DOI: 10.1111/apha.13080
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying blood pressure reduction by dietary inorganic nitrate

Abstract: Nitric oxide (NO) importantly contributes to cardiovascular homeostasis by regulating blood flow and maintaining endothelial integrity. Conversely, reduced NO bioavailability is a central feature during natural ageing and in many cardiovascular disorders, including hypertension. The inorganic anions nitrate and nitrite are endogenously formed after oxidation of NO synthase (NOS)-derived NO and are also present in our daily diet. Knowledge accumulated over the past two decades has demonstrated that these anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 264 publications
(321 reference statements)
4
57
1
Order By: Relevance
“…However, there was no reduction in diastolic BP after BRJ supplementation compared to PLA supplementation. A lowering of blood pressure after BRJ ingestion is consistent with previous reports 4,27 , with the mechanisms that underpin this effect likely to be multifaceted, but are largely believed to be NO-mediated 28 . The magnitude of BP reduction in the current study is likely to be of clinical relevance 29,30 .…”
Section: Discussionsupporting
confidence: 89%
“…However, there was no reduction in diastolic BP after BRJ supplementation compared to PLA supplementation. A lowering of blood pressure after BRJ ingestion is consistent with previous reports 4,27 , with the mechanisms that underpin this effect likely to be multifaceted, but are largely believed to be NO-mediated 28 . The magnitude of BP reduction in the current study is likely to be of clinical relevance 29,30 .…”
Section: Discussionsupporting
confidence: 89%
“…In support, several human studies have reported a significant contribution of NO to reactive hyperemia in the microvasculature . Another possible explanation for the positive effects of BRJ on microvascular reactivity in hypertensives may be the inhibition of vascular NADPH oxidase by increased normalNO3, resulting in reduced generation of free oxygen species and less scavenging of shear stress‐induced NO …”
Section: Discussionmentioning
confidence: 80%
“…However, the outcomes of this sub-study were defined post-hoc, hence there were no measures taken to ensure a consistent and comparable lifestyle (physical activity and dietary habits) from baseline to follow-up. Components of the NO pathway are sensitive to dietary intake of arginine (5), nitrite and especially nitrate (25), which is found in high levels in certain vegetables and is known to lower blood pressure (9).…”
Section: Limitations and Methodological Considerationsmentioning
confidence: 99%